VOC Emissions from Cork Products for Indoor Use - Horn, W.; Ullrich, D.; Seifert, B. (Indoor Air, 1998)
Abstract Complaints about unpleasant odour from wall, ceiling and floor coverings made of composite cork, induced chamber tests to study the emissions of volatile organic compounds (VOC) from composite cork products for indoor use. Emissions of phenol and furfural were found to be high, particularly those from cork parquet. Emission factors after 1 week ranged from 150 to 650 μg m−2 h−1 and from 15 to 350 μg m−2 h−1 for phenol and furfural, respectively, and decreased only slowly over time, by a factor of approx. 10 for a 6-month period. The ranges of emission factors were found to be similar for some solvents such as cyclohexanone or toluene which are constituents of varnishes used to protect cork surfaces. The emission of furfural may result from chemical reactions in the cork during the production process or may be caused by additives such as binders.
The following values have no corresponding Zotero field: publisher: Munksgaard International Publishers
Keywords: Chamber measurements; Composite cork; Emission factors; Furfural; Phenol